1990
DOI: 10.1021/bi00487a007
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the large hydrophobic amino acids to the stability of staphylococcal nuclease

Abstract: To quantitate the contributions of the large hydrophobic residues in staphylococcal nuclease to the stability of its native state, single alanine and glycine substitutions were constructed by site-directed mutagenesis for each of the 11 leucine, 9 valine, 7 tyrosine, 5 isoleucine, 4 methionine, and 3 phenylalanine residues. In addition, each isoleucine was also mutated to valine. The resulting collection of 83 mutant nucleases was submitted to guanidine hydrochloride denaturation using intrinsic tryptophan flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
368
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(409 citation statements)
references
References 30 publications
38
368
3
Order By: Relevance
“…The mden value asymptotically decreases with increased hydrophobicity. Changes in mden have previously been observed in conventional mutagenesis experiments at position 23 in nuclease (Shortle et al, 1990). The change in mden values, under the Schellman theory discussed above, suggests decreased surface area in the nonnative state(s) of nuclease as the hydrophobicity is increased.…”
Section: The Nonnative States Of Staphylococcal Nucleasementioning
confidence: 66%
See 1 more Smart Citation
“…The mden value asymptotically decreases with increased hydrophobicity. Changes in mden have previously been observed in conventional mutagenesis experiments at position 23 in nuclease (Shortle et al, 1990). The change in mden values, under the Schellman theory discussed above, suggests decreased surface area in the nonnative state(s) of nuclease as the hydrophobicity is increased.…”
Section: The Nonnative States Of Staphylococcal Nucleasementioning
confidence: 66%
“…Changes in m&fl have been observed for a large number of variants of staphylococcal nuclease (Shortle & Meeker, 1986;Green et al, 1992). Based on the correlation between changes in mden values and changes in stability, Shortle and colleagues have concluded that amino acid changes can affect the structure and free energy of the denatured state (Shortle et al, 1990). It is also possible to account for changes in mden by postulating a three-state mechanism ( N + + I -U).…”
Section: The Nonnative States Of Staphylococcal Nucleasementioning
confidence: 99%
“…However, there is a more relevant interpretation of changes in slope value. It has been postulated that changes in mGuHCl can be attributed to changes in the amount of solventaccessible hydrophobic surface area exposed during the transition between the native and denatured states (Schellman, 1978;Shortle et al, 1990;Dill & Shortle, 1991). According to this interpretation, higher slope values are found in those proteins that expose more hydrophobic surface area in the denatured state relative to the amount exposed in the native state.…”
Section: Discussionmentioning
confidence: 99%
“…The data was treated as a two-state model for reversible denaturation in which each protein molecule exists as folded or unfolded, whereas intermediate states are only transiently populated. Data analysis was carried out as previously published (Shortle et al, 1990;Stites et al, 1995). This analysis yields three parameters: a protein's stability to reversible denaturation (AGHZ0), the rate of change of free energy with respect to GuHCl concentration (rnGuHCI or d(AG)/d [GuHCI]), and the concentration of guanidine hydrochloride at which half the protein molecules are denatured (C,,,).…”
Section: Fluorescence Solvent Denaturationsmentioning
confidence: 99%
“…Conserved hydrophobic and/or small residues (Fig. I ) are known to contribute to S. aureus SNase protein stability (Shortle et al, 1990;Green et a!., 1992). Variants containing substitutions of Gly-107 or Ala-I32 are among the most unstable of SNase mutants (Green et a!., 1992), and it is notable that these are among the most conserved residues of SNase homologues, including those in pl00 orthologues (Fig.…”
Section: Snase-homologous Domains In P100mentioning
confidence: 99%